Physicians’ attitudes towards patients with substance-related disorders predict training needs in addiction medicine: challenges and opportunities for strengthening the global addiction medicine workforce - W. J. Lucas Pinxten; Efi Fitriana; Darius Jokūbonis; Virginija Adomaitiene; Darius Leskauskas; Giel J.M. Hutschemaekers; Cornelis A.J. De Jong (BMC Medical Education)
Abstract Background Substance use disorders (SUD) prevalence rises. Barriers to the expansion of global addiction workforce are a lack of qualified addiction physicians and healthcare providers’ negative attitudes/stigmatization towards patients with SUD (PWSUD), negative impacting treatment outcomes. Attitudes towards PWSUD and professional competence are associated. In order to confirm this association and to develop a stigma-focused model for strengthening global addiction services, this study explores the relationship between professional attitudes towards PWSUD and perceived competence. Methods The MCRS, measuring professionals’ attitudes towards patients with SUD, and the AM-TNA, measuring perceived training needs and competence gaps, were used to study the association between attitudes and competence. We used Pearson correlation, multiple regression, and PROCESS path analysis in a cross-sectional study design in a convenience sample of addiction physicians trained in The Netherlands (Dutch) (N = 70) and in Lithuanian (Lithuania) (N = 75) to explore this association and a possible moderation effect of the Gender and Country of Origin variables among addiction caregivers. Results We found a significant positive correlation between the total score of both scales: R = 0.537, p < 0.001. The MCRS predicted the three AM-TNA subscales significantly p < 0.001, and Gender did not influence the association between the two scales. The Country of Origin variable and its combination with the MCRS total score did strengthen the association between the MCRS and two AM-TNA subscales: medical- (p < 0.001) and practical aspects of perceived addiction competence (p < 0.05). Conclusions Knowledge and skills influence attitudes, while attitudes predict these: they are intertwined and mutually reinforcing, meaning that addiction physicians with positive attitudes are likelier to have and want better-developed addiction knowledge and skills. To improve addiction services and reduce stigma, combining the MCRS and the AM-TNA could reveal specific SUD competence gaps and offers an opportunity to model the design of an integrated, stigma-focused, addiction training or intervention approach. Future research should focus on the longitudinal use of the combined scales, assess individual professionals’ progress, and compare and combine self-reported competencies and attitudes with validated external assessments of learning, attitudes, self-efficacy and cognitive dissonance.